Prognostic Significance of Immune Checkpoints HLA-G/ILT-2/4 and PD-L1 in Colorectal Cancer - Chen, Qiong-Yuan; Chen, Yu-Xin; Han, Qiu-Yue; Zhang, Jiang-Gang; Zhou, Wen-Jun; Zhang, Xia; Ye, Yao-Han; Yan, Wei-Hua; Lin, Aifen (Frontiers in Immunology, 2021)
Immune checkpoint inhibitors (ICIs) have become a promising area of research for cancer treatment. In addition to the well-known ICIs targeting PD-1/PD-L1, HLA-G/ILT-2/-4 is relatively new immune checkpoint that has been evaluated in early clinical trials in patients with advanced solid tumors. In this study, the expression of HLA-G (n=157), ILT-2/4 (n=82), and PD-L1 (n=70) in epithelial cell adhesion molecule (EpCAM)-positive colorectal cancer (CRC) cells was analyzed by multicolor flow cytometry, and the prognostic significance of these molecules was evaluated. In EpCAM+ CRC cells, the median percentages of HLA-G, ILT-2, ILT-4, and PD-L1 were 14.90%, 67.70%, 8.55% and 80.30%, respectively. In addition, a positive correlation was observed between them (all p<0.001). Higher levels of these immune checkpoint proteins are associated with lymph node metastasis. In addition to the AJCC stage (p=0.001), Kaplan-Meier survival analysis showed that higher levels of HLA-G (p=0.041), ILT-2 (p=0.060), ILT-4 (p<0.001), PD-L1 (p=0.012), HLA-GILT4 (p<0.001) and ILT-2ILT-4 (p<0.001) were significantly associated with shorter survival of CRC patients. When CRC patients were stratified by early and advanced AJCC stages, HLA-G levels were only related to the survival among CRC patients with early disease stage (p=0.024), while ILT-4 levels were significant for both CRC patients with early (p=0.001) and advanced (p=0.020) disease stages. Multivariate cox regression analysis revealed that advanced AJCC stage (HR=2.435; p=0.005) and higher ILT-4 levels (HR=2.198; p=0.063) were independent risk factors for poor outcomes in patients with CRC. In summary, among the immune checkpoints, HLA-G/ILT-2/4 and PD-L1, ILT-4 is the most significant prognostic indicator of CRC. This finding indicated that a combination of immunotherapy strategies, such as ILT-4 blockade, could improve the clinical outcomes in patients with cancer. Moreover, multicolor flow cytometry can be employed as a reliable and efficient, alternative to immunohistochemistry, for evaluating the immune checkpoint proteins expressed in tumor lesions.